2020
DOI: 10.1109/access.2020.2979883
|View full text |Cite
|
Sign up to set email alerts
|

CMOS Backplane Pixel Circuit With Leakage and Voltage Drop Compensation for an Micro-LED Display Achieving 5000 PPI or Higher

Abstract: Micro-displays based on micro-LEDs are becoming more and more attractive in AR/MR (Augmented/Mixed Reality) applications. A display size of 0.5 to 0.7-inch is preferred, with 5,000 PPI (Pixel Per Inch) or higher. Due to this pixel density and size, a CMOS (Complementary Metal-Oxide-Silicon) backplane is an ideal solution to drive these pixelized micro-LEDs. As the required pixel size gets smaller, the design of the appropriate pixel circuit becomes more challenging. The simplest 2T1C (2 transistors & 1 capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 17 publications
(22 reference statements)
0
16
0
Order By: Relevance
“…It is difficult to achieve small pixelation at the sub-micron level for micro-display, and the pixel size directly affects the resolution of the device. The flip-chip technology usually is used for the hybrid integration of silicon-based pixel integrated circuits, but the pixel sizes generated by this method are usually more than 50 μm 27 . Zhang et al reported a wafer level batch manufacturing method based on silicon integrated circuits 27 .…”
Section: Micro-led and Inkjet Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to achieve small pixelation at the sub-micron level for micro-display, and the pixel size directly affects the resolution of the device. The flip-chip technology usually is used for the hybrid integration of silicon-based pixel integrated circuits, but the pixel sizes generated by this method are usually more than 50 μm 27 . Zhang et al reported a wafer level batch manufacturing method based on silicon integrated circuits 27 .…”
Section: Micro-led and Inkjet Printingmentioning
confidence: 99%
“…The flip-chip technology usually is used for the hybrid integration of silicon-based pixel integrated circuits, but the pixel sizes generated by this method are usually more than 50 μm 27 . Zhang et al reported a wafer level batch manufacturing method based on silicon integrated circuits 27 . A 4-inch red, green and blue monochrome active-matrix micro-LED (AM-μLED) micro-display with high brightness and the pixel density of more than 5000 PPI was successfully fabricated by this method.…”
Section: Micro-led and Inkjet Printingmentioning
confidence: 99%
“…The T-switch model minimizes V DS which helps reducing the subthreshold current [27], [28]. In this scheme, V DS of the switches is divided and then the discharging speed of C 1 and C 3 are decreased until C 0 and C 2 are fully discharged, respectively.…”
Section: B Led Driver Stagementioning
confidence: 99%
“…Since the backlight display is a device that is first used to emit light and is also displayed, the LED display device backlight has high brightness, long life, low power consumption, rich colors, low power consumption, low operating voltage, and easy miniaturization after the first light. The backlight integrated circuit control board has many significant advantages such as compatibility and matching, and it is one of the first applications of light-emitting display devices in the backlight liquid crystal display system on the large-size computer screen [16][17]. For details, see Figure 2…”
Section: Principle Of Led Full-color Displaymentioning
confidence: 99%